2005
DOI: 10.1071/sr04049
|View full text |Cite
|
Sign up to set email alerts
|

Competitive sorption reactions between phosphorus and organic matter in soil: a review

Abstract: The incorporation of organic matter (OM) in soils that are able to rapidly sorb applied phosphorus (P) fertiliser reportedly increases P availability to plants. This effect has commonly been ascribed to competition between the decomposition products of OM and P for soil sorption sites resulting in increased soil solution P concentrations. The evidence for competitive inhibition of P sorption by dissolved organic carbon compounds, derived from the breakdown of OM, includes studies on the competition between P a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
313
3
53

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 548 publications
(379 citation statements)
references
References 121 publications
10
313
3
53
Order By: Relevance
“…Ci. Solo, 38:1337Solo, 38: -1349Solo, 38: , 2014 soil acidification by the release of H + (Guppy et al, 2005), which was observed in the surface layers.…”
Section: Resultsmentioning
confidence: 99%
“…Ci. Solo, 38:1337Solo, 38: -1349Solo, 38: , 2014 soil acidification by the release of H + (Guppy et al, 2005), which was observed in the surface layers.…”
Section: Resultsmentioning
confidence: 99%
“…), v.67, n.4, p.465-471, July/August 2010 occurred because of the solubilization and migration of phosphates caused by rain water infiltration, as well as due to the mineralization of P-organic following decomposition of cover crops and soybean residues (Bayer and Mielniczuk, 1999;Guppy et al, 2005). A better distribution of soluble P may occur due to an increase in organic P forms resulting from the decomposition of the root systems from preceding crops (Rheinheimer et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Guppy et al (2005) relatam que entre os ácidos orgânicos mais ativos à disponibilização de P estão: cítrico, oxálico, glucôncio, lático e málico. Ácidos húmicos e fúlvicos, compostos mais estáveis e de longa persistência na fração orgânica do solo, também podem competir pelos sítios de adsorção.…”
Section: Introductionunclassified